Enhancing Students' Critical Thinking Through Discovery Learning Using Social Media as a Learning Tool in the Selection of Building Materials Based on Local Wisdom - Husain Faridl Muhammad; Dianti Zulfa; Okcter Vinny; Hutagaol Meidi Heiber; Zaitun Zaitun; Nevrita Nevrita (SHS Web of Conferences)
This study aims to enhance students' critical thinking skills in selecting building materials based local wisdom, using Discovery Learning model through use of social media as learning aid at SMKN 3 Tanjungpinang. The focus of research is improving critical thinking in selection of building materials that suitable for geographical conditions of Tanjungpinang and their availability in surrounding environment, while considering adaptation to natural disaster risks. The research method employed is Classroom Action Research with six stages of Discovery Learning: stimulation, problem statement, data collection, data processing, verification, and generalization. This study involves 30 students from Building Modeling and Information Design program. Quantitative research conducted, with data collected through observation, pre-test, and post-test. The results of study show 85% of students demonstrated good critical thinking, based observation results and comparison of pre-test and post-test outcomes. This approach proven effective in facilitating interactive learning relevant to local geographical conditions and local wisdom.